INNOVATIVE STRATEGIES IN MODERN CLINICAL MEDICINE: FROM ARTIFICIAL INTELLIGENCE TO HIGH-TECH SURGICAL RECONSTRUCTION - Давронова Муслимахон Равшан кизи; Очилдиева Азиза Олимжон кизи (Bright Mind Publishing, 2026)
The modern development of medicine in the Republic of Uzbekistan is characterized by the deep integration of fundamental scientific research and advanced clinical technologies. The transition to personalized medicine requires a rethinking of the pathogenetic mechanisms of common diseases, the introduction of digital diagnostic algorithms, and the improvement of surgical techniques. This analytical report presents a synthesis of nine key areas of medical research, covering rheumatology, cardiology, metabolic surgery, environmental toxicology, and reproductive medicine.
Keywords: research, covering rheumatology, cardiology, metabolic surgery, environmental toxicology, and reproductive medicine.